ANALISIS KARBOKSIMETIL SELULOSA DARI BAKTERI Acetobacter xylinum DAN Acetobacter sp. RMG-2 - Ruth Melliawati; Apridah Cameliawati Djohan (BERITA BIOLOGI, 2013)
Bacterial cellulose has long been manufactured and used for industrial purposes and health. Bacterial cellulose more profitable than the cellulose plants because during the manufacturing process, they do not harm the environment. The purpose of this study was to identify differences of cellulose produced by Acetobacter xylinum and Acetobacter sp. RMG-2 from that produced by plants. The study was also aimed to determine superiority of carboxymethyl cellulose (CMC) produced by those bacteria. The medium HB was prepared for the production of cellulose from both bacteria. Bacterial cellulose preparation was carried out to obtain solid fine powder, followed by manufacturing carboxymethyl cellulose through several stages to obtain CMC powder. CMC analysis was performed for both bacteria and plants targeted on the surface structure of cellulose, the density of solids, viscosity CMC and functional groups. As a result, the surface fiber cellulose plants had a wider space than fiber cellulose bacterium. The density of solids of CMC A. xylinum, A. sp. RMG-2 and plant were 30.9998 g/cm3, 0.0079 g/cm3 and 0.9978 g/cm3 respectively. Viscosity of the CMC were of 5.78 cP, 5.25 cP and 5.91 cP for each A. xylinum,A. sp. RMG-2 and plant. CMC functional groups of bacteria has met the parameters of success as indicated by the infrared spectrum since it formed a methyl group, carboxyl group and the group of sugar. Cellulose Acetobacter sp. RMG-2 and A. xylinum cellulose can replace plants through the process of compound alkalization with sodium hydroxide, because the compound can lower the level of density of pores of cellulose fibers. The CMC resulting from bacterial cellulose as good as CMC plant and had characteristics resembling CMC plant.